Resveratrol and ivacaftor are additive G551D CFTR‐channel potentiators: therapeutic implications for cystic fibrosis sinus disease. Issue 1 (27th August 2018) - Cho, Do‐Yeon; Zhang, Shaoyan; Lazrak, Ahmed; Grayson, Jessica W.; Peña Garcia, Jaime A.; Skinner, Daniel F.; Lim, Dong Jin; Mackey, Calvin; Banks, Catherine; Matalon, Sadis; Woodworth, Bradford A.
Abstract : Background: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene result in defective Cl − transport and cause chronic bacterial infections in the upper and lower airways of cystic fibrosis (CF) patients. Ivacaftor is a CFTR potentiator that improves Cl − transport in CF patients with at least 1 copy of the G551D mutation. Resveratrol is also a potent CFTR potentiator that increases determinants of mucociliary transport. The objective of this study is to determine whether resveratrol and ivacaftor improve Cl − secretion in G551D CFTR over either agent alone. Methods: Fisher rat thyroid cells (FRT) transfected with G551D CFTR and human sinonasal epithelial cells (HSNE) containing the CFTR G551D mutation were subjected to pharmacologic manipulation of transepithelial ion transport in Ussing chambers. Activity was further evaluated using whole‐cell patch clamp methods in G551D FRT cells. Results: In G551D FRT cells, resveratrol (100 μM) and ivacaftor (10 μM) significantly increased Cl − transport (change in short‐circuit current, δISC = μA/cm 2 ) compared with single‐agent and dimethylsulfoxide vehicle controls (resveratrol + ivacaftor 4.97 ± 0.57 vs ivacaftor 0.74 ± 0.12 vs resveratrol 2.96 ± 0.52 vs control 0.74 ± 0.12; p < 0.001). Maximal Cl − secretion (20 μM forskolin) was also significantly enhanced ( p < 0.0001). Activity was confirmed in G551D HSNE (resveratrol + ivacaftor 4.48 ± 0.39 vs ivacaftor 1.05 ± 0.11 vs. resveratrol 0.84 ± 0.3 vs control, 0.0 ± 0.02; p < 0.001), and whole‐cell patch clamp analysis in G551D FRT cells (resveratrol + ivacaftor −2535 ± 179.3 pA vs ivacaftor −1408.9 ± 101.3 pA vs resveratrol; −766.2 ± 71.2 pA; p < 0.0001). Conclusion: Additive improvement in G551D CFTR‐mediated Cl − secretion suggests that resveratrol could enhance ivacaftor therapy in these patients and improve CF‐related rhinosinusitis.